Implementasi Sistem Manajemen Kepegawaian (SAPA ASN) di BKPSDM Kabupaten Bantul - Angga, Novita Retno; Supardal, Supardal (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
SIMPEG is organized to manage personnel data quickly, precisely and accurately to support personnel administration management policies. The Bantul Regency Government has built and developed a web-based SIMPEG with the name SAPA ASN (State Civil Apparatus Integrated Service Application System) since 2017. In practice there are still various problems, including that there are still different main sets for this policy, as well as implementation which is still ongoing. There is a group of ASN who still do not understand the benefits of the policy, and also the changes in data and its dynamics are still not in sync with ASN data in the national civil service section. The research method used is qualitative descriptive, namely wanting to describe the phenomenon being studied in depth. The object of the research is the implementation of the SIMPEG SAPA ASN policy in Bantul Regency. The research subjects were BKPSDM leaders, SIMPEG operators and ASN as system users. Data collection techniques using observation, interviews and documentation. Technical data analysis starts from data identification, data reduction, data interpretation, research conclusions, and to determine the validity of the data, data triangulation is also carried out from observations, interviews and documentation data. The research results show that the implementation of the SIMPEG SAPA ASN policy at BKPSDM in Bantul Regency has gone quite well, this cannot be separated from the capacity of the implementers which is sufficient to support the implementation of the policy. Judging from the perception and consistency of policy implementers and policy makers, it is also relevant so that there is no gap between the two. Success is also due to the support of adequate supporting infrastructure and the availability of budget to maintain and repair system supporting hardware. The implementation of SIMPEG helps all ASN in Bantul, especially in storing data, making data changes and other personnel information.